Main active components of Si-Miao-Yong-An decoction (SMYAD) attenuate autophagy and apoptosis via the PDE5A-AKT and TLR4-NOX4 pathways in isoproterenol (ISO)-induced heart failure models. (February 2022) - Liao, Minru; Xie, Qiang; Zhao, Yuqian; Yang, Chengcan; Lin, Congcong; Wang, Guan; Liu, Bo; Zhu, Lingjuan
Abstract: Heart failure (HF), the main cause of death in patients with many cardiovascular diseases, has been reported to be closely related to the complicated pathogenesis of autophagy, apoptosis, and inflammation. Notably, Si-Miao-Yong-An decoction (SMYAD) is a traditional Chinese medicine (TCM) used to treat cardiovascular disease; however, the main active components and their relevant mechanisms remain to be discovered. Based on our previous ultra-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF-MS) results, we identified angoriside C (AC) and 3, 5-dicaffeoylquinic acid (3, 5-DiCQA) as the main active components of SMYAD. In vivo results showed that AC and 3, 5-DiCQA effectively improved cardiac function, reduced the fibrotic area, and alleviated isoproterenol (ISO)-induced myocarditis in rats. Moreover, AC and 3, 5-DiCQA inhibited ISO-induced autophagic cell death by inhibiting the PDE5A/AKT/mTOR/ULK1 pathway and inhibited ISO-induced apoptosis by inhibiting the TLR4/NOX4/BAX pathway. In addition, the autophagy inhibitor 3-MA was shown to reduce ISO-induced apoptosis, indicating that ISO-induced autophagic cell death leads to excess apoptosis. Taken together, the main active components AC and 3, 5-DiCQA of SMYAD inhibit the excessive autophagic cell death and apoptosis induced by ISO by inhibiting the PDE5A-AKT and TLR4-NOX4 pathways, thereby reducing myocardial inflammation and improving heart function to alleviate and treat a rat ISO-induced heart failure model and cell heart failure models. More importantly, the main active components of SMYAD will provide new insights into a promising strategy that will promote the discovery of more main active components of SMYAD for therapeutic purposes in the future. Graphical Abstract: ga1